Unveiling Pachacamac : New Hypotheses for an Old Andean Sanctuary - Marcone Flores, Giancarlo (Book collections on Project MUSE., 2022)
"This volume synthesizes 25 years of new data and hypotheses on the sacred Andean site of Pachacamac, a sanctuary that has an enduring presence in Peruvian history and plays a pivotal role in the formation of current views about religion and thought in the pre-Hispanic period"--